Mathematical model of hybrid precast gravity frames for smart construction and engineering - Park, S.; Hong, W.; Kim, S.; Wang, Xiangyu (Hindawi Publishing Corporation, 2014)
© 2014 Seon-Chee Park et al. The structural stability, constructability, economic feasibility, environmental-friendliness, and energy efficiency of hybrid composite frame systems have been demonstrated by practical application and research. A hybrid composite frame system combines the economy of precast concrete structures with the constructability of steel frame structures, including erection speed. Novel composite frames will ultimately maximize the efficiency of structural design and facilitate construction. This paper presents hybrid precast frames, which are precast composite frames based on a simple connection between precast concrete columns and beams. The hybrid precast frames designed to resist gravity loading consist of PC columns, PC beams, and steel inserted in the precast members. Steel sections located between the precast columns were simply connected to steel inserted at each end of the precast beams. Dynamic analysis of a 15-story building designed with the proposed composite frame was performed to determine the dynamic characteristics of a building constructed of hybrid frames, including frequencies and mode shapes.